Role of estradiol and C-reactive protein levels on genitourinary syndrome in menopausal women - Siregar, Muhammad FG.; Terauchi, Masakazu; Tobing, Immanuel DL.; Lubis, Roni B.; Azmeila, Selly; Pasaribu, Hotma P.; Prabudi, Oky; Ardiansyah, Edy; Effendi, Iman H. (Narra Sains Indonesia, 2024)
Menopause leads to decreased estradiol levels affecting tissue health and causing local inflammation in the genital organs and urinary tract. The rise of blood C-reactive protein (CRP) levels in menopausal women may indicate systemic inflammation associated with estradiol decline. The aim of this study was to determine the relationship between serum estradiol and CRP levels on genitourinary syndrome in menopausal women. A cross-sectional study was conducted among menopausal women who had not experienced menstruation for at least 12 consecutive months at Prof. dr. Chairuddin P. Lubis Hospital, Medan, Indonesia, in 2023. Estradiol and CRP levels were measured using enzyme-linked immunosorbent assay (ELISA) and the presence of genitourinary syndrome was assessed using the Menopause-Specific Quality of Life (MENQOL) questionnaire. The mean levels of estradiol and CRP were compared to menopausal women with and without genitourinary syndrome with the Mann-Whitney test. To assess the correlation between estradiol and CRP levels, and between their levels with the presence of genitourinary symptoms, the Spearman correlation test was used. The genitourinary syndrome was reported in 25% of the total included menopausal women. Our data indicated that the mean estradiol levels were not significantly different between menopausal women with and without genitourinary syndrome (9.13±2.47 pg/mL vs 18.96±31.23 pg/mL, p=0.881). The mean serum CRP level of menopausal women with genitourinary syndrome (9.72±6.30 mg/L) was higher than that of women without the syndrome (2.09±1.26 mg/L) with p<0.001. In addition, serum CRP level, not estradiol, was correlated with the symptom score of genitourinary syndrome. This study highlights that to identify and manage genitourinary syndrome, monitoring of CRP levels is essential in menopausal women.